A study on biofilm production and antifungal drug resistance among Candida species from vulvovaginal and bloodstream infections - Tulasidas S (Infection and Drug Resistance, 2018)
Sanyuktha Tulasidas,1 Pooja Rao,2 Sevitha Bhat,2 Radhakrishna Manipura1 1Department of Microbiology, Kasturba Medical College, Manipal Academy of Higher Education, Mangalore, Manipal, India; 2Department of Microbiology, Kasturba Medical College, Manipal Academy of Higher Education, Manipal McGill Center for Infectious Diseases, Mangalore, Manipal, India Introduction: Candida species, one among the opportunistic fungi, has become a common pathogen causing vaginal thrush and nosocomial bloodstream infections (BSIs). This study aims to evaluate the prevalence and antifungal susceptibility of various Candida species and slime production by Candida species in BSIs and vulvovaginal candidiasis (VVC). Materials and methods: A total of 176 samples were collected for a period of 1 year. Antifungal susceptibility testing and biofilm production testing were performed by the Kirby-Bauer method and crystal violet assay, respectively. Results: Out of 176 samples, 74 (42%) were from BSIs and 102 (58%) were from VVC. The biofilm production was comparatively high in blood isolates, 55 (74%), than cervical isolates, 45 (44%). Increase in the trends of non-albicans Candida (NAC) species was seen in our setup. Good susceptibility rates were seen among Candida species, 82.38% to voriconazole and an increasing resistance pattern of 26.13% to fluconazole. Conclusion: Speciation of Candida becomes important as the prevalence of NAC is increasing. Antifungal susceptibility testing by the disk diffusion method is cost effective and should be adopted in routine testing as there is an increasing azole resistance, especially in invasive NAC infections. In this study, there was no correlation of antifungal drugs with the biofilm production. Keywords: biofilm, Candida, azoles, vulvovaginal, bloodstream infections